Kaizen Costing and Quality Academic Administration Services Case Study: Bureau of Academic Administration in Trilogy University 2019 - Nurisa Anzani; Muhammad Zamzami; Aulia Nurazizah; Lely Dahlia (Asia Pacific Fraud Journal, 2021)
The purpose of this study is to explain the application of kaizen costing to the Academic Administration Bureau of the University of Trilogy. Kaizen costing is a concept that aims to reduce costs, strengthen brands, increase market share, increase information exchange within the company, increase profits, reduce capacity utilization, improve employee quality and productivity, and make gradual and continuous improvements to operational activities. Trilogy University Academic Administration Bureau was the object of research and involved employees of the Academic Administration Bureau and Trilogy University students from 2014 - 2019. This study used primary and secondary data. Primary data obtained through questionnaires and interviews, the preparation of the questionnaire considering the concept of 5S in kaizen costing namely Seiri, Seiton, Seiso, Seiketsu, Shitsuke. The results of this study indicate that based on respondents of the Trilogi University Academic Administration employee respondents suggest that only Seiketsu and Shitsuke affect quality of service of the Trilogy University Academic Administration Service. While the results based on student respondents indicate that Seiri, Seiton, Seiketsu, and Shitsuke affect the effectiveness and efficiency of the service of the Academic Administration Bureau of the University of Trilogy.